UPAYA UNITED NATIONS CHILDREN’S FUND (UNICEF)DALAM MENANGANI PROSTITUSI TERHADAP ANAK DI FILIPINA TAHUN 2008-2011 - Rika Mustika; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study describes the efforts of UNICEF in addressing childprostitution in the Philippines. UNICEF began providing assistance to thePhilippines in November 1948, since then UNICEF and the Philippinegovernment has become a partner in protecting children and women who arecommercial sex workers in the Philippines. Philippines especially children agedaround 11 to 15 years who netted into a prostitution. UNICEF in the Philippineshas more than 66 people who work to promote and protect children's rights,UNICEF aims to provide the best quality of life for every child in the Philippinesthrough programs that help them to survive and thrive. The main program is aprogram of the UNICEF education, health, nutrition, and prevention of HIV andAIDS.This study describes the phenomenon by linking political and economic power aswell as with government and non-government policy by using the perspective ofthe International Organization. This study used descriptive research methods andqualitative analysis of data obtained from books, journals, theses, and theses andinternet website.Keywords: UNICEF, Child Prostitution,Efforts of UNICEF, Filipina